Aplikasi Pasta Gigi Yang Mengandung Baking Soda Untuk Meningkatkan Ph Saliva Dalam Mencegah Karies Pada Murid SDN 2 Mata Ie - Cut Ratna Keumala; Mardelita, Sisca (Poltekkes Kemenkes Aceh, 2022)
Caries are a dental hard tissue disease in the form of a demineralization process of dental hard tissue caused by bacterial activity in the oral cavity. Caries are the most common dental and oral health problem in society. One of the causes of caries is bacteria. Bacteria break down carbohydrate substrates attached to the oral cavity and form plaque. Bacterial activity continues as the pH of the oral cavity becomes more acidic. This condition causes decalcification of the enamel, forming white spot lesions that signal the start of the caries process. Prior to the counseling, a pre-test was first conducted, then interviewed the students to measure their level of knowledge. The realization of activities can increase salivary pH by using toothpaste containing baking soda in preventing caries and increasing students' ability to brush their teeth properly and correctly. The results of community service activities showed that knowledge before counseling was in a good category as many as 7 students (23.3%) increased by 26 students (86.7%) after counseling. It was concluded that there was an increase in children's knowledge about toothpaste containing baking soda which had the effect of increasing salivary pH. Keywords: Caries, Saliva pH, Baking Soda